KESANTUNAN TINDAK TUTUR BERTANYA PEMBAWA ACARA INDONESIA LAWYERS CLUB DI STASIUN TELEVISI TVONE - Ramadhani, Nia Elsa; Manaf, Ngusman Abdul; Juita, Novia (Jurnal Bahasa dan Sastra, 2018)
This research was conducted to describe (1) the realization of the principle of politeness by the Indonesian Lawyers Club host on TVONE to act questioning and (2) the context of the use of the principle of politeness in the act of said speech. This research type is qualitative research by using descriptive method. This research data is in the form of a questioning question done by the host of Indonesia Lawyers Club which aired during March 2016. The data source of this research is a video of ILC event on 01, 08, 15, 22 and 29 March 2016 which has been downloaded in social media youtube. The data analysis process is done with 3 steps. (1) identify data in the form of questioning, (2) classify data that realize the maxims of courtesy principles, and (3) describe the context of the use of principles of politeness in acts of speech asked. Based on the results of data analysis obtained two research findings. First, the principle of politeness realized by the ILC host during March 2016, found the use of 4 maxims, ie (a) 38 data maximization of wisdom, (b) 11 data maxim of praise, (c) 8 data maxim of humility, and (d) 33 data maximization of inference. Second, the context of the use of the principle of politeness in speech acts asks (a) higher and less familiar speakers tend to be used maxim of wisdom, (b) higher and higher speakers tend to be used maxim of wisdom, (c) speakers of equal position and unfamiliar is used maximally, and (d) lower-level speakers and not yet familiar tend to be used maxim of inference. Thus, it can be concluded that the realization of the principle of civility most often realized by ILC hosts is the maxim of wisdom that tends to be used in the context of lower-level speakers and not yet familiar.Keywords: Politeness Principle, Talkshow, Indonesia Lawyers Club